FIBROSA PRZECIW FAIRBAIRN - POLSKA SPÓŁKA, IZBA LORDÓW I PRAWO RZYMSKIE - Marzec, Łukasz (Zeszyty Prawnicze, 2017)
Fibrosa v. Fairbairn. Polish Company, House of Lords and the Roman Law Summary This paper deals w ith the development of the British doctrine of unjust enrichm ent, influenced to some extent by condictiones of the Rom an law. At the beginning of the XXth century the common law recognized two contradictory views on the restitution of „solutio indebiti”. According to „coronation” cases losses arising from performance of a contract up to the moment of a frustration - should lie where they fall, which was unjust and did not meet the needs o f trade. This attitude was changed by the House of Lords when two very similar cases: Cantiere and Fibrosa were heard. Fibrosa S.A. was a Polish com pany that sued Fairbairn for the money paid in advance for machine parts that were finally not delivered. The reason why the contract was frustrated was the outbreak of the war. The case was decided on the basis of the Rom an law condictio causa data causa non secuta and became a precedent for the modern com m on law world. The paper also discusses the suitability of using the causa data causa non secuta, where causa fm ita seems to be a better solution, and the question whether causa data causa non secuta could be used outside contracts.